UJI EKSPERIMENTAL TIPE TWIN WATERJET THRUSTER MENGGUNAKAN MATERIAL STAINLESS STEEL 304 - Hasdiansah Hasdiansah; Ferzy Ersandy; Boy Rollastin; Muhammad Subhan; Faiz Maulana Akbar (Universitas Muhammadiyah Metro, 2026)
Maritime is a vital sector that highly depends on ship propulsion systems to support mobility and maritime security. One of the developing propulsion technologies is the waterjet thruster, which provides advantages in maneuverability, efficiency, and resistance to cavitation for high-speed vessels. This study aims to experimentally investigate the performance of a twin waterjet thruster made of stainless steel 304. The prototype was designed using SolidWorks software with a configuration of 12-blade inlet, 3-blade impeller, and 12-blade outlet, and tested using a 22 HP combustion engine at 2,300 rpm in a water test tank. The results showed thrust values of 23 kg, 24 kg, and 25 kg with an average of 24 kg or 235.44 N. The variations were influenced by water flow conditions, pump pressure, and engine stability. Overall, the twin waterjet thruster made of stainless steel 304 proved to be effective, consistent, and has the potential for further development with higher engine speeds or different drive types for real ship applications.